Cardiac arrest in myocardial infarction with non-obstructive coronary artery (MINOCA) secondary to thyroid dysfunction. Issue 2 (10th February 2023) - Omar, Ahmed Moemen A; Knott, Kristopher; Saba, Magdi M; Lim, Pitt O
Abstract : A man in his 40s who was previously well had an out-of-hospital cardiac arrest. Postresuscitation ECG showed ST-elevation myocardial infarction (MI). Emergency coronary angiogram revealed MI with non-obstructive coronary arteries (MINOCA) with evidence of spasm in the right coronary artery. Both his echocardiogram and cardiac MRI revealed a normal heart. Further workup showed markedly elevated free T4 (99.5 pmol/L) and free T3 (26.7 pmol/L) with low thyroid stimulating hormone (<0.02 pmol/L) in keeping with thyroid storm. He also had an elevated adjusted calcium level (2.84 mmol/L), which could have contributed to his coronary artery spasm. His peak troponin T was elevated at 798 ng/L (<14) suggesting myocardial damage. He was treated with propylthiouracil, steroids, beta-blocker, calcium channel blocker and intravenous fluids. The patient achieved a full recovery and was discharged home. This is an unusual case of thyroid dysfunction resulting in coronary artery spasm, cardiac arrest and MINOCA.